2013
DOI: 10.1111/cch.12103
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index (BMI)‐for‐age and health‐related quality of life (HRQOL) among high school students in Tehran

Abstract: More than one-third of adolescents were overweight and obese. BMI-for-age was inversely correlated to adolescent self-reported HRQOL. Based on adolescents' perspective, overweight and obese adolescents had poorer HRQOL compared with normal weight adolescents. Intervention studies are needed to improve the HRQOL of overweight and obese adolescents in Tehran.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
2
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 31 publications
4
28
2
6
Order By: Relevance
“…Adolescents in group N had a worse perception of their oral health than did those in group O because there were positive associations with Eating, Cleaning mouth and Smiling ( Table 3). The low perception of health-related quality of life in group O differs from that of other studies 31,32 , in which overweight/obesity was associated with worse quality of life. However, in this study, group O adolescents had lower dental caries activity than did adolescents in group N, which, in turn, could explain the low perception in the Child-OIDP.…”
Section: Discussioncontrasting
confidence: 94%
“…Adolescents in group N had a worse perception of their oral health than did those in group O because there were positive associations with Eating, Cleaning mouth and Smiling ( Table 3). The low perception of health-related quality of life in group O differs from that of other studies 31,32 , in which overweight/obesity was associated with worse quality of life. However, in this study, group O adolescents had lower dental caries activity than did adolescents in group N, which, in turn, could explain the low perception in the Child-OIDP.…”
Section: Discussioncontrasting
confidence: 94%
“…This finding indicates that negative emotions and rest related issues are the most well-known issues among Iranian children and these health problems should be considered by health-care professionals. [31] In our study, age was not related to HRQOL in primary school children of Tehran. Although in previous studies (in children 8-18) HRQOL declined with age [32] this finding could be due to selecting participant from a narrow range of age in this study.…”
Section: Discussioncontrasting
confidence: 50%
“…Additionally, in this study we found that the total and physical summary scores were lower in the underweight group, particularly among older children. This contrasts with several studies which report no significant difference in HRQOL between underweight and healthy weight children [25, 34, 35]. Again, this could be linked to cultural influences; if heaviness is taken to be a sign of health, growth and prosperity, then underweight may indicate poor health and poverty, and thus lead to a lower quality of life.…”
Section: Discussionmentioning
confidence: 60%